IMPLEMENTASI EKONOMI SYARIAH PADA MODEL BISNIS APLIKASI GO JEK - Wijaya, Rahmat Guna (Jurnal Keuangan dan Perbankan Syariah, 2023)
The digital economy is one of the things that marked the development and economic growth in the future, characterized by increasingly rapid development of business or trade transactions using the internet service as a medium to communicate, collaboration and cooperation between companies or individuals. In the development of the digital economy in Indonesia at this time, obtained the fact of the existence of the implementation principle profit and lost sharing. in accordance with the Islamic economic system brought in Islamic civilization. A trading business like that run between the company Go Jek, investor, investors, and the drivers Go Jek who runs a shuttle transportation service of people, goods and services with the use of information technology in the application system internet network. As for the principle for the results is done in accordance with the rules of Sharia in the economic system of Islam is the use of mudharabah and musyarakah contract. Mudharabah and musyarakah is business model with sharing or partnerships between two or more parties to run businesses.